2018
DOI: 10.1007/s13203-018-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetalization of glycerol with acetone over various metal-modified SBA-15 catalysts

Abstract: Several catalysts containing metals such as Al, Zr, Ti and Nb were incorporated in SBA-15 with Si/M ratio = 20 using the hydrothermal process. These catalysts were evaluated for their reactivity during acid-catalyzed condensation of glycerol with acetone to yield a mixture of branched compounds, namely (2,2-dimethyl-[1,3] dioxane-4-yl)-methanol (solketal) and 2,2-dimethyl-[1,3] dioxane-5-ol, which are being used as fuel additives. The synthesised catalyst samples were characterized by ICP-AES analysis, N 2 ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…In addition, reverse, as opposed to forward reaction is faster and therefore water equilibrium does not have any special role. By this reasoning and those suggested in references (Ferreira et al, 2010; Reddy et al, 2011; Royon et al, 2011; Ortiz et al, 2012; Menezes et al, 2013; Nanda et al, 2014b; Aghbashlo et al, 2018, 2019; Ammaji et al, 2018; Fatimah et al, 2019), water equilibrium is not reached nor is it considered necessary for this current proposed kinetic model. Since water is formed during the experimental reaction process, experimentally the effect of water has not been studied in the current work.…”
Section: Kinetic Modeling Of the Reaction Systemsupporting
confidence: 51%
“…In addition, reverse, as opposed to forward reaction is faster and therefore water equilibrium does not have any special role. By this reasoning and those suggested in references (Ferreira et al, 2010; Reddy et al, 2011; Royon et al, 2011; Ortiz et al, 2012; Menezes et al, 2013; Nanda et al, 2014b; Aghbashlo et al, 2018, 2019; Ammaji et al, 2018; Fatimah et al, 2019), water equilibrium is not reached nor is it considered necessary for this current proposed kinetic model. Since water is formed during the experimental reaction process, experimentally the effect of water has not been studied in the current work.…”
Section: Kinetic Modeling Of the Reaction Systemsupporting
confidence: 51%
“…Hydrophobic catalysts, such as hafnium and TUD-1 zirconium on TUD-1, are very prospective for glycerol to solketal. Ammaji et al (2017) [62] also reported a similar observation, as the Zr-SBA-15 was the most active and selective catalyst. Dmitriev et al (2016) [63] reported that zeolite beta was the most active solid acid catalyst as compared to amberlist-35 and cation-exchange resin (KU-2-8) [62].…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 58%
“…Ammaji et al (2017) [62] also reported a similar observation, as the Zr-SBA-15 was the most active and selective catalyst. Dmitriev et al (2016) [63] reported that zeolite beta was the most active solid acid catalyst as compared to amberlist-35 and cation-exchange resin (KU-2-8) [62]. The zeolite beta applied was a commercial one from zeolyst with SiO 2 /Al 2 O 3 of 25 and a zeolite beta made by Angarsk.…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 58%
“…The acidic strength of solid acid catalysts in the NH 3 -TPD pro les can be classi ed into three regions depending on their strength in the temperature range. These acidic sites are denoted as weak (150-300 °C), moderate (300-450 °C), and strong (450-650 °C) 12 . The desorption peak of NH 3 -TPDfor AAC-CC shows a weak acidic site at 147.1 °C while showing a sharp peak at 605°C with higher intensity having strong acidic strength ( Figure 11).…”
Section: Resultsmentioning
confidence: 99%